Blending Formal and Informal Learning within an International Learning Network - Cook, J.; Basiel, A. S.; Mitchell, W. L.; Mohammed, T. H.; Commins, R. (Proceedings of the International Conference on Networked Learning, 2006)
Recent work on online, formal and informal learning raises important questions. To what extent can online learning communities also be informal learning communities? What 'community building' issues are raised in the context of international learning networks? In the paper we will (i) briefly describe a new case study of a learning network (part of the JISC 'Case Studies in e-Learning Practice' project), (ii) present a framework that builds on the notions of people, policies and purpose but which is supplemented by notions of informal learning, and finding 'common ground', (iii) illustrate the framework using examples from the case study and follow-up research, and (iv) conclude by drawing out key issues raised by our work.